Muatan Keterampilan Berpikir Tingkat Tinggi pada Buku Pelajaran Bahasa Indonesia SMP Kelas VIII - Alkarima, Oryza; Sumarwati, Sumarwati; Suryanto, Edy (GERAM: Gerakan Aktif Menulis, 2022)
Learning materials should optimally accommodate higher-order thinking skills (HOTS) to train students to think critically. The research aimed to describe the content of HOTS in Indonesian language textbooks for eighth grade found in the materials, examples, and exercises. Bloom's taxonomic cognitive theory by Anderson and Krathwohl was used in this study. This type of research was qualitative research with a content analysis approach. The data collection techniques were document analysis and interviews. Data analysis techniques employed model intertwined with the stages of data collection, data reduction, data presentation, withdrawal of conclusions, and return to data collection—techniques of presenting the results of data analysis using informal methods. Data sources were documents that include an Indonesian language textbook for eighth grade published by the Ministry of Education and Culture and Mahir Berbahasa Indonesia textbook published by Erlangga, and informants were Indonesian language teachers. Data validity test techniques used triangulation methods and data sources. The results showed HOTS provided in the textbook published by Kemendikbud, which was 3.8% of the material, 53% of example, and 38.9% of exercise. From the textbook published by Erlangga, HOTS provided 12.6% of the material, 44% of the example, and 33.2% of the exercise. The results reveal that the textbook published by the Ministry of Education and Culture provides more high-level thinking skills content, and Erlangga's book provides more detailed information about students' ability to think at high levels.